Análise morfológica do sistema digestório de recém-nascidos de ratas prenhes submetidas à ingestão de etilenotioureia - Lemos, Sidney Pereira Pinto [UNIFESP] (2010)
INTRODUCTION: Congenital abnormalities are important causes of death and severe sequelae, and improvement of the knowledge of chronic diseases such as aganglionosis and other abnormalities of the myenteric plexus is of great importance. OBJECTIVES: To morphologically, histologically and immunohistochemically evaluate abnormalities of the myenteric nervous system in the gastrointestinal tract of newborns from pregnant rats exposed to ethylenethiourea (ETU). METHOD: Newborns from female Wistar rats that had received ETU on the eleventh day of pregnancy were studied. Cesarean section was performed on the twentieth day of pregnancy. After birth, the newborns were analyzed and the congenital abnormalities were identified and recorded. Morphometry was performed on the muscle layer, and abnormalities in the ganglionic cells of the myenteric plexus and interstitial cells of Cajal (ICC) were evaluated, using HE, P S-100, C-KIT and neuron-specific enolase. The data obtained were expressed as means for each group. RESULTS: The newborns from the female rats exposed to ETU presented abnormalities of embryo formation, with musculoskeletal abnormalities in 100% of the newborns, anorectal abnormalities in 86%, taillessness in 71% and short or vestigial tail in 29%. The histopathological analysis showed atrophy of the muscle layer associated with lesions of myenteric plexus, in all segments of the gastrointestinal tract, characterized by reduced density in the ganglionic cells and ICC and thinning of the musculature, thus suggesting that the process occurred linearly. CONCLUSIONS: 1) ETU was efficient in producing various types of congenital abnormalities in the newborns from the exposed female rats. 2) ETU was efficient in producing severe abnormalities in the myenteric plexus of the gastrointestinal tract. 3) ETU promoted atrophy of the muscle layer throughout the gastrointestinal tract. 4) The nerve abnormalities in the myenteric plexus and muscle abnormalities occurred concomitantly throughout the gastrointestinal tract.